فعالية برنامج تدريبي لتحسين وتنمية نطق المفردات اللغوية لدى الأطفال ذوي الإعاقة العقلية بالمرحلة الابتدائية - السواح، صالح عبدالمقصود (مؤسسة التربية الخاصة والتأهيل, 2018)
هدفت هذه الدراسة إلى التعرف على تحسين وتنمية نطق المفردات اللغوية لدى الأطفال ذوي الإعاقة العقلية والكشف عن مدى فعالية البرنامج وطبقت على عينة (١٠) أطفال من ذوى الإعاقة العقلية القابلين للتعلم من مدرسة التربية الفكرية بمدينة منيا القمح بمحافظة الشرقية، تراوحت أعمارهم بين (٧ -١٠) عاماً وقد تم استخدام مقياس ستانفورد بينيه لقياس الذكاء (الصورة الرابعة) إعداد وترجمة: لويس مليكة (١٩٩٨) مقياس اختبار اللغة إعداد: نهلة الرفاعي (٢٠٠٦) البرنامج التدريبي لتحسين وتنمية نطق المفردات اللغوية للأطفال ذوى الإعاقة العقلية إعداد: الباحث. وأسفرت النتائج عن ارتفاع تحسين وتنمية أداء ونطق المفردات اللغوية لدى المجموعة التجريبية بعد تطبيق البرنامج مقارنة بالمجموعة الضابطة، واستمرار الأثر الإيجابي للبرنامج على المجموعة التجريبية خلال فترة المتابعة.
This research aims at recognizing the improvement and development of vocabulary utterance among mentally retarded children, as well as the effectiveness of a training program that has been applied to a sample of 10 mentally retarded educable children in Menya Alkamh Special Needs School, Sharkia Governorate, Egypt. The children's ages ranged between 7- 10 years old. The researcher used the fourth edition of Stanford-Binet Intelligence Test, translated by Luis Melekah (1998), as well as the Language Test Scale prepared by Nahla Alrefai (2006), along with the training program for improving and developing vocabulary utterance among mentally retarded children, which has been prepared by the researcher. The results reveal an increase in the level of vocabulary utterance and performance among the experimental group after applying the training program, compared to the control group. The positive effect of the program on the experimental group continued through the follow-up period.
Keywords: البرامج التدريبية -- المفردات اللغوية -- الأطفال المعاقين -- الإعاقة العقلية -- المرحلة الابتدائية